2016
DOI: 10.1155/2016/1424193
|View full text |Cite
|
Sign up to set email alerts
|

Day of Surgery Admission in Total Joint Arthroplasty: Why Are Surgeries Cancelled? An Analysis of 3195 Planned Procedures and 114 Cancellations

Abstract: Background. Day of surgery admission (DOSA) is becoming standard practice as a means of reducing cost in total joint arthroplasty. Aims. The aim of our study was to audit the use of DOSA in a specialty hospital and identify reasons for cancellation. Methods. A retrospective study of patients presenting for hip or knee arthroplasty between 2008 and 2013 was performed. All patients were assessed at the preoperative assessment clinic (PAC). Results. Of 3195 patients deemed fit for surgery, 114 patients (3.5%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…From the point of view of socio-demographic characteristics, these are young patients with an average age of 40.1 years, which is similar to other African series and is explained by the youth of the population of the continent [4] [14] [15]. On the other hand, in developed countries, this average age is higher: 73 years for Dalton [8] in Ireland, and 61.5 years for Hori [11] in Japan. The sex ratio was 2.4 and is explained by the strong involvement of men in trauma.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…From the point of view of socio-demographic characteristics, these are young patients with an average age of 40.1 years, which is similar to other African series and is explained by the youth of the population of the continent [4] [14] [15]. On the other hand, in developed countries, this average age is higher: 73 years for Dalton [8] in Ireland, and 61.5 years for Hori [11] in Japan. The sex ratio was 2.4 and is explained by the strong involvement of men in trauma.…”
Section: Discussionsupporting
confidence: 69%
“…These causes are preventable in most cases [17] [18]. If in developed countries, postponements and cancellations are increasingly rare due to better organization of services [8] [11] [16] [19], in Africa, there are still high rates that vary between 23% and 40% [9] [18] [15]. In Burkina Faso, the phenomenon seems even more accentuated with rates reaching 46% [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the number of arthroplasties will increase dramatically in the coming period [4,5]. However, unexpected cancellation of scheduled TJA surgery is an unavoidable part of orthopedic practice [6,7]. The number of cancelled cases will also increase accordingly without available precautions.…”
Section: Introductionmentioning
confidence: 99%
“…Unnecessarily postponing a TJA surgery will not only worsen their suffering but could potentially affect the ultimate outcome [9,[13][14][15][16]. Meanwhile, the delay in the procedure itself or the fact that patients have another emerging medical problem to worry about can further contribute to their anxiety and depression [7,8,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to determine the benefits of adopting SDA, a process whereby elective surgical patients are admitted to the hospital on the day of their planned surgery [ [16] , [17] , [18] ]. SDA (also known as day of surgery admission [ DOSA]) it has been adopted globally and used for decades as a model to reduce the average length of stay and costs associated with surgery [ 19 ]. Many developed countries have introduced SDA as a part of their quality improvement projects for pediatric patients [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%